Biosyntheses of geranic acid and citronellic acid from monoterpene alcohols by Saccharomyces cerevisiae. Issue 6 (13th March 2021) - Ohashi, Yuka; Huang, Shuai; Maeda, Isamu
ABSTRACT: Geraniol is one of the important aromatic ingredients in alcoholic beverages. Bioconversions of geraniol to other terpenoids and genes involved in the oxidation of geraniol were investigated. Geranic acid and citronellic acid were detected in yeast culture, where geraniol or nerol was added. Addition of citral, a mixture of geranial and neral, resulted in the production of geranic acid and citronellic acid, whereas the addition of citral or citronellal resulted in the production of citronellic acid, suggesting that citronellic acid might be produced through the conversion of citral to citronellal followed by the oxidation of citronellal. Consumption of geraniol and production of geranic acid, citronellic acid, and citronellol were affected in adh1 Δ, adh3 Δ, adh4 Δ, and sfa1 Δ yeast strains, which possess single deletion of a gene encoding alcohol dehydrogenase. This is the first report of the bioconversion of monoterpene alcohols, geraniol and nerol, to geranic acid and citronellic acid in yeast culture. Graphical Abstract: